TRENDS AND PATTERNS IN PROBLEM-BASED LEARNING RESEARCH FOR ENGLISH LANGUAGE TEACHING: BIBLIOMETRIC STUDY - Rovikasari, Mala; Mutammimah, Heppy; Jati, Anida Fadhilah (UICELL, 2023)
This bibliometric study aims to explore the evolving landscape of research related to problem-based learning (PBL) in English language teaching (ELT). The research design comprehensively reviews academic publications from Google Scholar databases. The data is collected through Publish or Perish, and the analysis is conducted using bibliometric techniques. The research procedure consists of systematic literature searching and data extraction, followed by rigorous data analysis using Vosviewer. The bibliometric mapping using Vosviewer indicates fluctuating development in problem-based learning in English language teaching from 2015 to 2023, supported by 994 indexed publications on Google Scholar. The 30 patterns identified in this field form five dominant clusters: curriculum, English language teaching, experience, foreign language, learner, learning English, performance, task, ability, creativity, critical thinking skill, effectiveness, influence, learning model, outcome, active learning, challenge, interest, opportunity, practice, problem-based learning, systematic review, focus, inquiry, project, technology, total, higher order thinking skill, improvement, and perception. Keywords: Problem-based Learning, ELT, Bibliometric, Vosviewer, Publish or Perish